SAKRAMEN BAPTIS SEBAGAI SAKRAMEN KESELAMATAN DAN PERSEKUTUAN PARA MURID KRISTUS - Wilhelmus, Ola Rongan (Lembaga Penelitian STKIP Widya Yuwana, 2020)
Baptism is a sacrament instituted and used by God Himself through Christ to purify, sanctify and to save human being out of the power of evil spirit. Baptism celebration maintaining in a proper and faithful manner will be brought about the fullness grace and favor of God to the Catholic faithful. The experiences of the Catholic faithful regarding God’s grace and favor should not be only responded by full faith but also be properly responded by full action to bring it to the entire nations and human races. The Catholic Church as a communion of Christ disciples has been sent and guided by the Holy Spirit to spread out such grace and favor of God to all nations. Pastoral assembly of Surabaya Diocese conducted in 2019 strongly articulated that Baptism is a mean exactly used by God Himself to channel His grace and salvation to the entire human beings. Hence, the Disciples of Christ have to fully respond it by full faith and opened hart. Christ Himself has sent His disciples to collectively spread out the grace, favor and salvation of God to all over the world. This good news has to be brought firstly to the inner circle of the Catholic families, neighbours, communities, parishes, and diocese then to the society in general.